The Relationship Between Breakfast Habits and Learning Concentration Among Students at SMP Negeri 9 Padangsidimpuan - Siregar, Nurhanifah; Harahap, Lena Juliana (Bioedunis Journal, 2025)
Breakfast habits play a crucial role in supporting students’ cognitive function and learning concentration. This study aims to determine the relationship between breakfast habits and the level of learning concentration among students at SMP Negeri 9 Padangsidimpuan. The research employed a descriptive quantitative design with a cross-sectional approach. The sample consisted of 52 students selected through total sampling. Data were collected using questionnaires and analyzed using the chi-square test. The results showed that most students who regularly had breakfast demonstrated good learning concentration, while those who skipped breakfast tended to have decreased concentration. A significant relationship was found between breakfast habits and students’ learning concentration (p = 0.003). These findings confirm that breakfast not only affects physical health but also supports brain function in learning processes. Promotive interventions through nutrition education in schools are essential to foster healthy eating habits among school-aged children.